P210 Airways Resistance In Bronchial Challenge Testing. (10th November 2014) - Baxter, MAJ; Coates, D; Wilson, AM
Abstract : Introduction: Measurement of airways resistance is an alternative to spirometry to assess airflow obstruction. This can be measured by the interrupter technique (RInt) using a hand held device. We wished to know how RInt compared to forced expiratory volume in 1 second (FEV1) during a histamine challenge test. Methods: Twenty-nine (13 male) patients, aged 48.9 (SD 15.3) years, referred for a histamine challenge test were enrolled. Patients had measurement of RInt then FEV1 after administration of saline and following doubling concentrations of histamine from 0.06 mg/ml to 8 mg/ml. Extrapolation of the log dose-response curve was undertaken to calculate the concentration (Provocation Concentration – PC) causing an increase airways resistance of 20, 40, 60, 80, 100, 120, 140 and 160% (RInt PC1.2 to RInt PC2.6) and a reduction in FEV1 by 20% (FEV1 PC20). The number of patients with a negative challenge (i.e. PC > 8 mg/ml histamine) was calculated for FEV1 and each change in airway resistance. Patients assessed their procedure provoked symptoms of breathlessness, dizziness and tiredness on a 100 mm visual analogue scale. Results: Geometric (SD) PC20 for FEV1 was 1.87 (0.5) mg/ml with 11 patients having a negative challenge. A RInt PC2.0 had the best agreement with FEV1 PC20 (Kappa 0.39 (p = 0.024)). There is a significant negative correlation between RInt and FEV1 (r = -0.94). The respective mean (SD) breathlessness, dizziness and tiredness scores for RInt were 26(4) mm, 18(3) mm, 22(4) mm and for spirometry were 40(4) mm, 27(5) mm, 31(5)mm. There was a significant (p < 0.05) difference for breathlessness. Conclusion: RInt was tolerated better than spirometry. A doubling of airways resistance had the best agreement with PC20 FEV1.